Grand challenges in organizational justice, diversity and equity - Konrad, Alison M.; Bhardwaj, Arjun (Frontiers in Organizational Psychology, 2023)
This inaugural article founding the Frontiers Journal Section on Organizational Justice, Diversity and Equity highlights four broad areas requiring further research in our field. First, organizational justice and DEI share common threads, and there is considerable room for work that conceptually integrates these two areas of study. Specifically, we need research that helps us understand how organizations as inequality-producing systems create and maintain perceptions of (un)fairness when individuals receive unequal rewards for their contributions, particularly in diverse workplaces. Furthermore, research is needed to enhance understanding of how to create and maintain high levels of organizational justice for both marginalized and predominant identity groups. Additionally, this is a space for empirical work that replicates prior findings, something that is essential to the development of science. It is also important to expand the scope of justice and DEI scholarship with a greater inclusion of research contexts from the Global South. Finally, Organizational Justice and DEI topics are inflamed in the contemporary U.S. context, and there is a need for investigation of how the societal context influences the development of our field.